The Influence of Work Experience and Training on the Performance of Ministry of Justice Employees" Dili, Timor-Leste. - Silva, Jose Da; Costa, Francisco Da; Costa, Juvenal Da; Halik, Abdul (Business Management, 2025)
This research concerns employees of the Ministry of Justice, Dili, Timor-Leste. The aim of this research is for researchers to examine the effect of work experience and training on work performance. With the population in this study being employees who work at the Ministry of Justice, with the number of employees who were respondents in this study totaling 85 people, the researcher used probability sampling with the Census technique, namely a population of 85 people was used as the respondent sample. The variables used are three (3) variables. Multiple linear regression analysis (Y = a + b1X1 + b2X2 + e) was used for analysis. The research results show that there is a positive and significant influence (sig) on the variables Work Experience, Training, Influence on Job Performance at the Ministry of Justice Dili Timor-Leste. So the results of this research are as follows: Y = 3.934 + 0.400 X1 + 0.429 Beta value 1 (b1) = 0.400 is the regression coefficient for Work Experience (X1), meaning that every change in the Ministry of Justice and an increase in work performance (Y) by an amount of 0.400 or 40.0% means that the Training variable (X2) is constant. beta value 2 (b2) = 0.429 is the regression coefficient for the Training variable (X2) meaning that there is a change in work performance at the Ministry of Justice. and an increase in work performance (Y) of 0.429 or 42.9%, and the value of e (Error) = Distraction error (the term disturbance) is 1.242, meaning the value of other variables that are not included in the formulation of this linear regression equation.